Distinction of Inheritance of Parusah Land Rights in West Seram Regency, Province of Maluku - Pikahulan, Rustam (DIKTUM: Jurnal Syariah dan Hukum, 2024)
According to some indigenous peoples in Maluku, the existence of Parusah land is not as a usufructuary but as their land given to them by the king or customary leaders. Inheritance of parosah land in West Seram Regency mostly uses a collective inheritance system, namely by being enjoyed together. This type of research is empirical juridical research, namely legal research related to the enactment or implementation of normative legal provisions in social life (law in action). This study aims to see how customary law works in society through the customs of indigenous peoples in the West Seram Regency, especially in the Parusah land inheritance system. Based on the results of the analysis, the researcher concluded that the inheritance of parosah land carried out by the people of West Seram Regency was customary inheritance law. The inheritance system of parosah land in Seram Part District depends on the family agreement after the parents have died or the will of the parents during their lifetime, so that the inheritance in the form of company land can be inherited by way of sharing, collectively, or by using the mayoral system.